Correlation of carotid intimal media thickness with activity and duration of Rheumatoid arthritis using carotid Doppler Ultrasonography - Kumar, P. Shravan; Bhargavi, M; T, Abhilash; Mythili, Lakshmi (International Journal of Medical Research and Review, 2016)
Background: Cardiovascular cause is the leading cause of mortality in RA and this has been attributed to accelerated atherosclerosis. Indirect evidence of accelerated atherosclerosis in RA comes from studies using carotid artery intima media thickness (CIMT) as a marker of atherosclerotic burden and cardiovascular risk. Aims: To assess carotid intima-media thickness in patients with rheumatoid arthritis by using Doppler ultrasound and to study the correlation between carotid intima-media thickness and the duration and severity of rheumatoid arthritis. Materials and Methods: A total of 30 rheumatoid arthritis patients were enrolled during 2 year study. Patients satisfying the modified American Rheumatology Association criteria (1987) were included .Those with hypertension, cardiac disease, and diabetes mellitus were excluded. Subjects were divided into three groups (each group consist of 10 patients) based on disease duration. For measurement of carotid intimal medial thickness B-mode USG scan using 7.5 MHz probe is used. Results: The mean value of common carotid intima media thickness (CCIMT) was significantly higher in the study group (0.8 mm) when compared to control group (0.59 mm) (p value < 0.001). Total carotid intima media thickness (i.e., mean of total CIMT of CCA, ICA, and ECA) was significantly higher in the study group (0.76 mm) when compared to control group (0.57 mm) (p value < 0.001). Conclusion: The study shows a significant directly proportional relation between carotid intima media thickness to longer duration of disease.